Comparison of language and visual-motor developments between exclusively and non-exclusively breastfed infants through cognitive adaptive test/clinical linguistic and auditory milestone scale - Lesmana Syahrir; Eddy Fadlyana; Sjarif Hidajat Effendi (Indonesian Pediatric Society, 2009)
Background Provision of adequate nutrients is needed in theearly year oflife to support the most rapid growth and development period in infant's life. Moreover, warm and responsive parent-child interaction associated with breastfeeding is beneficial for optimal child development.Objective The objective of this study was to compare the language and visual-motor developments between exclusively breast-fed and non-exclusively breast-fed infants.Methods This historical cohort study was performed from Mayto June 2009. Study subjects consisted of 6-month-old infantslived in Puskesmas Garuda operational area. Language and visual-motor development were measured by cognitive adaptive test/clinical linguistic &auditory milestone scale (CAT/CLAMS). The differences of CAT /CLAMS scores between groups were analyzed with Mann-Whitney test.Results There were 39 exclusively breastfed and 39 non-exclusively breastfed infants enrolled in this study. No significant differences were found between the two groups concerning the subject or their parents characteristics. Mean CAT/CLAMS score of the exclusively breastfed infants was 8.34 points higher than that of the non-exclusively breastfed infants (P=0.002). Similar outcomes were found in language and visual-motor scales which were higher in the exclusively breastfed infants with the differences of9.82 points (P=O.OOl) and 6.85 points (P=0.039), respectively.Conclusion Exclusively breastfed infants has higher language andvisual-motor developmental quotient score than non-exclusivelybreastfed infants.